(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
Six inbred lines of maize (1) H, (2) A, (3) I, (4) T, (5) E, (6) M, obtain (45) double hybrids result from ( 15) single hybrids. The seeds of Double hybrids were sown in experiments comparison using randomized completely block design (RCBD) in three replication in the field of technical agricultural college It was conducted during 2021 autumn to estimate general and specific combining ability parents and double hybrids to study traits like (number of days to silking and tasselling, plant height, ear diameter and length, number of rows per ear, number of grains per ear, 300 grain weight, yield per plant.depended comparison Analysis of variances for double hybrids were differ significantly at 1% for all studied traits. Result from comparison analysis variances double hybrids showed presence effects additive genetic and non additive genetic effects for all traits. The inbreed ( A ) effects desirable of general combining ability for all characters. Followed by inbreed ( I ) which showed desirable general effects for all characters except height plant. The performance of double hybrid was good for all characters of interaction in arrangement (ij) (kl) and then could be used in future breeding programs.